Fluid structural interface analysis of gas flow in oil and gas transmission pipe - Yap, Huey Tyng (2013)
A solution interface of fluid structural problems which are the coupling Computational Fluid Dynamics (CFD) analysis has become more tractable through the accessibility of High Performance Computing. Mainly, with the demand of reducing the vibration problem which contributed from the coupling interaction between the fluid flow and the structure, the Fluid Structural Interface (FSI) analysis is performed to find out the stress and strain of the structure. A pipeline test rig is built in lab scale for accuracy correlation purpose by studying the dynamics characteristic and response of the structure. The pipeline is measured and analyzed in order to observe its dynamics characteristic through modal analysis. The result from A.NSYS Modal Analysis is then correlated with the result from measurement analysis. It has been found that the accuracy of the results can be up more than 90%. The computational model that passed the accuracy comparison is then been analyzed to obtain the stress and strain of the structure through ANSYS Transient Structural and CFX coupling analysis. The results indicate that the pipeline test rig is having a maximum stress of 20.9kPa and maximum strain of 5x106. Results from ANSYS Modal Analysis show that the reliability of the computational model and ANSYS FSI analysis can determine the stress and strain which are occurring on the pipeline system.